Determinants of treatment completion among rural smear positive pulmonary tuberculosis patients: a cross-sectional survey conducted in south-western Uganda - Mulogo, Edgar Mugema; Nahabwe, Christopher; Bagenda, Fred; Batwala, Vincent (CrossMark, 2017)
Treatment completion among tuberculosis patients remains low across various regions of Uganda,despite implementation of directly observed treatment short course. This study evaluated the determinants of treatment completion in a rural health sub-district of south western Uganda. The level of treatment completion was higher than the national average, with service- related determinants identified as being critical for ensuring treatment completion. These data provide further evidence for the need to provide ongoing counselling support to tuberculosis patients. Enhancing the opportunities for counselling of tuberculosis patients should therefore be rigorously promoted as an approach to increase treatment completion in rural settings.
Treatment completion among rural smear positive pulmonary tuberculosis patients.
Keywords: Tuberculosis, Treatment completion, Determinants, Rural Uganda.